MELD SCORE AND HEPATIC ENCEPHALOPATHY AS PREDICTORS OF MORTALITY IN PATIENTS WITH DECOMPENSATED ALCOHOLIC LIVER CIRRHOSIS - Rančić, Andrija; Radisavljević, Mirjana; Milanović, Marko; Todorović, Stefan; Bajić, Lazar (Acta medicae Medianae, 2024)
Cirrhosis is the final stage of numerous chronic liver diseases. The disease most often occurs as a result of chronic alcohol consumption and infection with hepatitis C and B viruses. Over 3 million people die globally as a result of alcohol consumption. Prognostic scores have been developed to estimate survival rates. The MELD score (model for end-stage liver disease) is used today in the prognosis of short-term survival of patients with decompensated liver cirrhosis. This prospective/retrospective study was conducted on a sample of 56 patients (52 male and 4 female) with an average age of 55.23 ± 10.82. MELD score values were calculated at the end of hospitalization and correlated with defined treatment outcomes. Based on the conducted receiver operating characteristic (ROC) analysis, cut-off values of MELD score over 23.5 were statistically significant in the prognosis of mortality. Of the total examined population, 72% of patients with a score higher than the obtained cut-off value died. The total number of patients with hepatic encephalopathy was 34 (61%), of which 23 died. ROC analysis in the group of patients with hepatic encephalopathy revealed a cut-off value of the MELD score of 30.5, which is statistically not significantly different from the cut-off value of the MELD score for survival. The male-to-female ratio in the subsamples of deceased and survived patients in this study was approximately equal. The cut-off value of the MELD score proved to be statistically significant in predicting short-term survival. The increase in the cut-off value of the MELD score in patients with hepatic encephalopathy was not statistically significant. In the group of patients with hepatic encephalopathy, 92% of patients died, although no statistically significant increase in the cut-off value of the MELD score was found.